The effectiveness of nutritional intervention(s) and the treatment of pressure ulcers— A systematic literature review. (21st February 2013) - Siang Choo, Tze; Hayter, Mark; Watson, Roger
Abstract : This review aims to evaluate the effectiveness of nutritional intervention in the treatment of pressure ulcers. Four databases were searched systematically using the keywords formulated and papers were selected according to inclusion and exclusion criteria. The literature search period included articles published from 1 January 2000 to 30 December 2011 (inclusive). Six papers on randomized controlled trials were retrieved. All six trials showed positive outcomes in pressure ulcer healing with nutritional interventions. Secondary outcomes such as lower number of dressings required, less time spent on dressing changes and lower occurrence of infections were reported. The main results emerged from this study generally supported the use of nutritional interventions in the treatment of pressure ulcers. Various methodological issues associated with these trials were highlighted. The implications for clinical practice need to bear in mind both the methodological problems raised and limitations of this review.